Growth kinetics and transmission dynamics of Borrelia afzelii in Ixodes ricinus - Pospíšilová, Tereza (Jihočeská univerzita, 2016)
Laboratory model for Lyme disease was used for a revision of Borrelia afzelii / Ixodes ricinus transmission cycle. The behaviour of B. afzelii in different phases of the transmission cycle was analyzed. The role of the tick vector I. ricinus in the transmission of B. afzelii was investigated.
Growth kinetics and transmission dynamics of Borrelia afzelii in Ixodes ricinus
Keywords: Borrelia; tick; Lyme disease; Ixodes ricinus; Borrelia afzelii; tick transmitted pathogens; transmission of Lyme disease; Borreliosis; Borrelia; tick; Lyme disease; Ixodes ricinus; Borrelia afzelii; tick transmitted pathogens; transmission of Lyme disease; Borreliosis